Explaining the Sociological Model of Women's Body Management Based on Cultural Capital and Media with Social Comparison Mediation (Case Study: Sanandaj ( - Ronak Dorokh; Hamed Nouri (زن در فرهنگ و هنر, 2020)
One of the issues in the field of body sociology is body management, which is widespread today among girls and women. It means people build social bodies by altering their physical appearance. The research method was applied in terms of purpose in the descriptive-analytical method. The research has used instruments including Bourdieu Cultural Capital Questionnaire and Researcher-Made Questionnaire of Women's Body Management Scale and Social Comparison of Gibbons and Bonk in 2019. The sample size was 382 women and girls aged 20-45 in the city of Sanandaj. The method was multi-stage cluster sampling. SPSS22 software and LISREL software were used for quantitative data analysis. The results showed that there is a significant relationship between variables of body management, cultural capital, media, and social comparison of mentioned variables. The sociological model of body management in women based on cultural capital and the media is mediated by social comparison mediation in Sanandaj. Social comparison with a impact coefficient of 0.45 can affect two variables of cultural capital that have had effects on the media variable of body management criterion. In urban women, social comparison is an essential source of information about body self-management, and social comparison processes fill the gap between self-talk and the concept of individual and inter-group identity.